The Role of Social Media Marketing, E-WOM, and Brand Trust in Glad2Glow Repurchase through Customer Satisfaction - Vina Septiana; Ali Ali (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the relationships of Social Media Marketing, Electronic Word of Mouth (E-WOM), and Brand Trust with Repurchase Intention through Customer Satisfaction among Glad2Glow consumers in Jepara Regency. Research Method: A cross-sectional survey involved 154 consumers selected through purposive sampling. Respondents had purchased Glad2Glow products at least twice and used social media. Data were analyzed using PLS-SEM with SmartPLS. Results and Discussion: The estimates indicated positive relationships between the three antecedents, Customer Satisfaction, and Repurchase Intention. E-WOM showed the greatest association with Customer Satisfaction, whereas Brand Trust had weak importance. However, Customer Satisfaction and Repurchase Intention failed to demonstrate discriminant validity because their indicators overlapped. The structural and mediation findings therefore remain provisional. Implications: Glad2Glow should prioritize credible reviews, informative social media communication, transparent information, and consistent product quality. Future studies should use distinct validated measures. Originality: This study evaluates digital marketing, consumer information, and brand-related confidence within an emerging Indonesian skincare context while identifying measurement redundancy that limits mediation conclusions.